Narrativa hipermedia en los diarios ecuatorianos El Universo y El Comercio: Un estudio comparativo - Alvarado Torres, Joselyn Alicia (2020)
For the realization of this case study, a comparative analysis of the hypermedia narrative that is currently used in the newspapers el universo and el comercio, which are two of the best-selling newspapers in the country, was aimed at analyzing the hypermedia narrative in the Ecuadorian newspapers, the universe and commerce: a comparative study. Once compared, it was possible to notice that the newspaper the universe uses publishing by the publishers taking responsibility for the comments issued, for its part, the newspaper trade uses the name of the journalist as a reference, in addition to this within the website of both sites they use graphic or striking photos of the event, digital videos and interviews with the important characters that are involved in relation to the news expressed or public. The inclusion of hypermedia narrative and the use of technological tools for the digital development of a newspaper in Ecuador is not yet developed, it is for this reason that traditional and non-hypermedia narrative continues to be used, despite posting audiovisual content. inclusion of hypermedia narrative and the use of technological tools for the digital development of a newspaper in Ecuador is not yet developed, it is for this reason that traditional and non-hypermedia narrative continues to be used, despite posting audiovisual content.